Applied crowd science - Still, G. Keith (Boca Raton, FL : CRC Press, 2022)
"Crowd sciences and risk analysis can drive the planning, licensing and safe operation for events and places of public assembly. This provides case studies and examples from around the world using DIM-ICE, RAMP analysis, risk and congestion mapping, and decision support analysis -- for event planners and managers, public administrators, urban and transportation designers, and emergency services"--
OCLC-licensed vendor bibliographic record.
Keywords: Crowds; Crowd control; Risk assessment; POLITICAL SCIENCE / Public Policy / City Planning & Urban Development; SOCIAL SCIENCE / Disasters & Disaster Relief